1991
DOI: 10.1128/jcm.29.2.346-354.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genus-specific epitope on the 60-kilodalton Legionella heat shock protein recognized by a monoclonal antibody

Abstract: A monoclonal antibody (MAb) immunoglobulin G2a (2125) was produced against a 60-kDa Legionella heat shock protein (HSP), recognizing a unique epitope common to all species of the genus Legionella. The antibody reacted in the immunoblot with 59 Legionella species and serogroups that were tested and showed no cross-reactivity with other bacteria, including Acinetobacter spp., Bordetella spp., Pseudomonas spp., Mycobacterium spp., and Escherichia coli. Two other MAbs (2122 and 2130) reacted with the 60-kDa Legion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

1991
1991
1998
1998

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…Although the most striking features of hsp60 molecules are their immunudominance and broad cross-reactivity, it has been shown that these proteins also contain genus-and species-specific epitopes (31). The monoclonal antibody, MAb 2528, used in this study was shown in extensive tests to recognize a species-specific epitope on the hsp60 of P. aeruginosa (2).…”
Section: Discussionmentioning
confidence: 99%
“…Although the most striking features of hsp60 molecules are their immunudominance and broad cross-reactivity, it has been shown that these proteins also contain genus-and species-specific epitopes (31). The monoclonal antibody, MAb 2528, used in this study was shown in extensive tests to recognize a species-specific epitope on the hsp60 of P. aeruginosa (2).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the organization of the groE operon in E. coli, whereas the analogous proteins in M tuberculosis are expressed from different operons (Shinnick 1987, Shinnick et al 1989. We could, however, not demonstrate any convincing heat-shock induced increase in expression of the 60 kL3 L. micdadei GroEL in the recombinant by Western blotting with a Legionella CA-specific monoclonal antibody (Steinmetz et al 1991). Radioactive incorporation of 35Smethionin during heat shock did result in a stronger expression of a 60 kD protein, which, however, could represent both the E. coli and the L. micdadei GroEL.…”
Section: Genetic Studies 63 Screening For Immunodominant Antigensmentioning
confidence: 56%
“…The same investigators raised three monoclonal antibodies against the L. pneumophila CA (Sampson et al 1991), but none of these were 100 YO specific to the Legionellaceae, and their use in a diagnostic test has not yet been presented. German researchers produced a monoclonal antibody (Steinmetz et al 1991) reactive with a genus-specific epitope on the L. pneumophila CA. This antibody (MAb 2125) did not perform adequately in an immunofluorescence test, but was found to be usell in a membrane immunoassay for identifLing Legionella colonies (Steinmetz et a1.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…L. pneumophila strains 040741 and 038695b.. legionellae without cultivation (6). In this study, we developed a straightforward and rapid colony blot assay based on this genus-specific MAb which makes it possible to screen hundreds of colonies in one test and to identify legionellae growing on agar medium in less than 2 h. Table 1 lists the strains used in this study.…”
Section: Atcc 35304mentioning
confidence: 99%
“…The production and characterization of the genus-specific MAb 2125 has been described previously (6). MAb 2125 recognizes a genus-specific epitope on the 60-kDa heat shock protein of all Legionella species.…”
Section: Atcc 35304mentioning
confidence: 99%